Assessment of Spawning Fecundity and Its Relationship with Body Parameters of Rainbow Trout (Oncorhynchus mykiss) and Brown Trout (Salmo trutta fario) - Bazaz, Asim Iqbal; Shah, Tasaduq H.; Bhat, Farooz A.; Ahmad, Irfan; Arab, Nafhat-ul-; Altaf, Maheen; Andleeb, Saima; Hafiz, Zaib; Shafi, Bisma; Shah, Azra (International Journal of Bio-resource and Stress Management, 2022)
The present investigations were carried out at Trout Culture Farm Laribal, Srinagar (J&K Govt.), India during December, 2020. Relationship between length-weight, spawning fecundity and relative fecundity was observed in rainbow trout (O. mykiss) and brown trout (S. trutta fario). The mean length of male rainbow trout was (38.77±1.38 cm) and mean length of (38.05±1.32 cm) was observed in female rainbow trout. While as, the mean length of male brown trout was (38.86±1.41 cm) and for female brown trout mean length of (37.98±1.30 cm) was observed. The mean weight of male and female rainbow trout recorded was 794.6±49.3 g and 766.3±64.3 g respectively, while as, the average weight of male and female brown trout was 772.7±41.4 g and 757.6±57.22 g respectively. The spawning fecundity female-1 of rainbow trout ranged from 2002−2804 eggs and mean relative fecundity of 3.13±0.12 g-1 body weight was observed and for brown trout the spawning fecundity female-1 fish ranged from 961 to 1604 eggs, with a relative fecundity of 1.41 g-1 body weight to 1.56 g-1 body weight. The present study recorded a significant positive correlation between total body length and total body weight of male rainbow trout (r=0.938, p<0.05) and total body length and total body weight of female rainbow trout (r=0.989, p<0.05) and for brown trout a significant positive correlation was recorded between total body length and spawning fecundity, body weight and spawning fecundity was observed. However, relative fecundity formed a significant negative correlation between total length, body weight and spawning fecundity in brown trout.